Childhood Age and Associations Between Childhood Metabolic Syndrome and Adult Risk for Metabolic Syndrome, Type 2 Diabetes Mellitus and Carotid Intima Media Thickness: The International Childhood Cardiovascular Cohort Consortium. Issue 8 (16th August 2017) - Koskinen, Juha; Magnussen, Costan G.; Sinaiko, Alan; Woo, Jessica; Urbina, Elaine; Jacobs, David R.; Steinberger, Julia; Prineas, Ronald; Sabin, Matthew A.; Burns, Trudy; Berenson, Gerald; Bazzano, Lydia; et al.
Abstract : Background: There is paucity of knowledge concerning the specific age in youth when the associations of metabolic syndrome (MetS) begin to be operative. Thus, we investigated the relation of age to the associations of childhood MetS with adult MetS, type 2 diabetes mellitus and high carotid intima‐media thickness. Methods and Results: Five thousand eight‐hundred three participants were analyzed in 4 cohort studies (Cardiovascular Risk in Young Finns, Bogalusa Heart Study, Princeton Lipid Research Study, Insulin Study). International cutoffs and previously used 75th percentile cutoffs were used for children to define MetS and its components. Mean follow‐up period was 22.3 years. Logistic regression was used to calculate risk ratios and 95% confidence intervals. Childhood MetS and overweight were associated with over 2.4‐fold risk for adult MetS from the age of 5 years onward. Risk for type 2 diabetes mellitus was increased from the age of 8 (risk ratio, 2.6–4.1; 95% confidence interval, 1.35–6.76 and 1.12–7.24, respectively) onward for the 2 childhood MetS criteria based on international cut‐off values and for childhood overweight. Risk for high carotid intima‐media thickness was significant at ages 11 to 18 years in relation to childhood MetS or overweight (risk ratio, 2.44–4.22; 95% confidence interval, 1.55–3.55 and 2.55–5.66, respectively). Continuous childhood MetS score was associated with adult MetS from the age of 5, with type 2 diabetes mellitus from the age of 14 and with high carotid intima‐media thickness from the age of 11 years onward. Conclusions: Adult MetS was predicted by MetS in childhood beginning at age 5. However, adult type 2 diabetes mellitus and subclinical atherosclerosis were not predicted by childhood data until after age 8. Body mass index measurement alone at the same age points provided similar findings.